Expanding relationship science to unpartnered singles: What predicts life satisfaction? - Walsh, Lisa C.; Gonzales, Ariana M.; Shen, Lucy; Rodriguez, Anthony; Kaufman, Victor A. (Frontiers in Psychology, 2022)
Singles are an understudied yet growing segment of the adult population. The current study aims to expand the lens of relationship science by examining the well-being of unpartnered, single adults using latent profile analysis. We recruited singles (N=4,835) closely matched to the U.S. census (ages 18-65; 57.5% female; 71.1% White; 14.5% Black; 13.8% Hispanic) for an exploratory cross-sectional survey using five variables that strongly predict well-being (friendship satisfaction, family satisfaction, self-esteem, neuroticism, and extraversion). All five variables significantly predicted life satisfaction for the full sample. Latent profile analyses detected 10 groups (or profiles) of singles. Half of the profiles were happy (above the full sample mean of life satisfaction) and half of the profiles were unhappy (below the mean). Each profile had its own unique patterns relating to personal relationships, self-esteem, and personality traits. The happiest profile had the best relationships, self-esteem, and personality, while the unhappiest profile had the worst relationships, self-esteem, and personality. The profiles in between these two extremes had more nuanced patterns. For example, one relatively happy profile in the middle had high friendship satisfaction but low family satisfaction, while an adjacent profile showed the opposite pattern. Overall, singles who had positive relationships—both with themselves and others—were happiest.